PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA SATUAN KERJA PELAKSANAAN JALAN NASIONAL WILAYAH III PROVINSI JAWA TIMUR - Pipiet Widayati; Sri Rahayu; Pompong B. Setiadi; Rifda Fitrianty (MANAJEMEN DEWANTARA, 2024)
This research is carried out in order to know: (1) the impact of competence on employee performance in the National Road Implementation Work Unitof Region III East Java Province, (2) the impact of work discipline on performance employees in the National Road Implementation Work Unit Region III East Java Province, and (3) The Simultaneous Impact of Work Discipline Competence and Competence on the performance of employees of the Region III National Road Implementation Work Unit East Java Province. The population of this study consisted of employees of the National Road Implementation Task Force Region III East Java Province which amounted to 125 people. Data be obtained using a questionnaire that has been tested for validity and reliability. The data analysis method used is multiple regression. The results of this study provide data that: (1) Competence has a positive effect on the performance of employees of the National Road Implementation Task Force Region III East Java; (2) Work discipline significantly affects employee performance in employees of the National Road Implementation Task Force Region III East Java Province (3) There is a simultaneous influence of ability and work discipline on the performance of employees of the National Road Implementation Task Force Region III East Java Province